Efeito do patrocínio às indústrias esportiva e criativa sobre o desempenho das empresas brasileiras de capital aberto - Alcântara, Jessica Nunes de (2015)
With this research, we aimed at verifying the influence of the sports and creative industries sponsorship strategy over the performance of public Brazilian companies in the period from 2007 to 2013. The sample consisted of 49 companies that have shares traded on the BM&FBovespa and have IBASE social reports. The nature of this study is quantitative and data were collected by means of the Economática ® database, IBASE social reports, administrative reports, social and sustainability reports annually published by the studied companies. The statistical techniques used to meet the proposed objectives were descriptive statistics, logistic regression and multiple regression. The results show that, among the amount of investment performed along the analysis period, 82% is destined for sponsoring culture and 18%, for sponsoring sports. In addition, the sector that most used the sponsorship strategy for sports and culture is the electricity sector, however, the sector that most invests, allocating a higher amount of financial resources, is the telecommunication sector. The investment in culture per year reaches two or three times that which is invested in sports, even in years of world sporting events, such as the Olympic Games or FIFA World Cup and Confederation Cup. The first logistic regression performed showed that among the specific traits of the firm, size and profitability have a positive relation with the probability of the company adopting the sponsorship strategy to sports and creative industries. The results also showed that company size, as well as industrial concentration of the sector in which the companies operate, have positive relation with the probability of the company adopting the sponsorship strategy to both industries, sports and creative. Finally, we observed that the sponsorship to sports, as well as to culture, has positive relation with the economic performance of the companies. The results of this work are relevant, given that they show the economic importance for companies that adopt sponsorship to sports and creative industries as a strategy.